2013
DOI: 10.3892/ijmm.2013.1291
|View full text |Cite
|
Sign up to set email alerts
|

Activity of antibacterial protein from maggots against Staphylococcus aureus in vitro and in vivo

Abstract: Maggots (larvae of Lucilia sericata) have shown therapeutic effects on refractory wounds infected with bacteria, yet the bacterial killing mechanisms are unclear. Herein, we report the isolation and purification of an antibacterial protein from maggots (MAMP). MAMP demonstrated inhibitory activity against both standard strains and clinically isolated antibiotic-resistant strains of Staphylococcus aureus in vitro. The topical use of MAMP effectively decreased the viability of S. aureus and promoted wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 34 publications
0
26
0
6
Order By: Relevance
“…In 2013, Chinese researchers described the isolation of antimicrobial protein from an extract of the homogenate of L. sericata larvae using an ultrafiltration procedure [33]. The crude material obtained was named “antibacterial protein from maggots” (MAMP).…”
Section: The Brief History Of the Search For Antimicrobial Agents mentioning
confidence: 99%
“…In 2013, Chinese researchers described the isolation of antimicrobial protein from an extract of the homogenate of L. sericata larvae using an ultrafiltration procedure [33]. The crude material obtained was named “antibacterial protein from maggots” (MAMP).…”
Section: The Brief History Of the Search For Antimicrobial Agents mentioning
confidence: 99%
“…Given the high forage and food value of Musca domestica, the cultivation of their larvae and pupae can alleviate the protein feed shortage (Akpodiete et al, 1997;Hwangbo et al, 2009;Iniguez-covarrubias et al, 1994;Miller et al, 1974;Ocio and Vinaras, 1979;van Huis, 2013;Yan et al, 2012;Zuidhof et al, 2003). Additionally, M. domestica larvae, or maggots, contain several biologically active substances, such as antimicrobial peptides, lectin and chitin Fu et al, 2009;Hou et al, 2007;Nayduch and Joyner, 2013;Tang et al, 2009;Wang et al, 2013;Zhang et al, 2013). The supplemental use of maggots in animal feed may improve animals' immune systems and reduce antibiotic usage Dong et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…A further investigation on antimicrobial activities of compounds released externally by L. sericata has confirmed the presence of a range of structurally diverse compounds, and most recently, research scientists in China have reported the isolation and purification of yet another antibacterial molecule from larval secretions [5]. This protein, MAMP, has a significant inhibitory effect on S. aureus and appears to work by disrupting the bacterial cell membrane [6]. In addition, another group of researchers have posited that over 45 antimicrobial peptides including lucifensin, lucimycin, attacins, cecropins, diptericins, proline-rich peptides, and sarcotoxins, are coded in L. sericata.…”
Section: Advances In Wound Disinfection By Medicinal Maggotsmentioning
confidence: 99%